Increased Frequency of Pink Bollworm Resistance to Bt Toxin Cry1Ac in China - Wan, Peng; Huang, Yunxin; Wu, Huaiheng; Huang, Minsong; Cong, Shengbo; Tabashnik, Bruce E.; Wu, Kongming (PLOS ONE, 2012)
Transgenic crops producing insecticidal proteins from Bacillus thuringiensis (Bt) kill some key insect pests, but evolution of resistance by pests can reduce their efficacy. The main approach for delaying pest adaptation to Bt crops uses non-Bt host plants as “refuges” to increase survival of susceptible pests. To delay evolution of pest resistance to transgenic cotton producing Bt toxin Cry1Ac, the United States and some other countries have required refuges of non-Bt cotton, while farmers in China have relied on “natural” refuges of non-Bt host plants other than cotton. The “natural” refuge strategy focuses on cotton bollworm (Helicoverpa armigera), the primary target of Bt cotton in China that attacks many crops, but it does not apply to another major pest, pink bollworm (Pectinophora gossypiella), which feeds almost entirely on cotton in China. Here we report data showing field-evolved resistance to Cry1Ac by pink bollworm in the Yangtze River Valley of China. Laboratory bioassay data from 51 field-derived strains show that the susceptibility to Cry1Ac was significantly lower during 2008 to 2010 than 2005 to 2007. The percentage of field populations yielding one or more survivors at a diagnostic concentration of Cry1Ac increased from 0% in 2005–2007 to 56% in 2008–2010. However, the median survival at the diagnostic concentration was only 1.6% from 2008 to 2010 and failure of Bt cotton to control pink bollworm has not been reported in China. The early detection of resistance reported here may promote proactive countermeasures, such as a switch to transgenic cotton producing toxins distinct from Cry1A toxins, increased planting of non-Bt cotton, and integration of other management tactics together with Bt cotton.